Legal implications Parental Responsibility Due to Electronic Agreements Made by Minors - Souhoka, Elma; Berlianty, Teng; Labetubun, Muchtar Anshary Hamid (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: The current era of globalization has resulted in very rapid technological developments, people are facilitated in meeting their needs through electronic transactions. However, the ease of conducting electronic transactions means that it can also be done by minors, this certainly has legal consequences from the electronic agreement made so that parents/guardians can be held accountable for the agreement.Purposes of the Research: The purpose of this study is how to enrich the understanding of parental responsibilities in electronic agreements carried out by minors.Methods of the Research: Normative legal research, with a statute approach and a conceptual approach.Findings of the Research: Results study This show that agreement electronics that are done by children under age , no legitimate in a way law based on Article 1320 of the Civil Code and Article 46 of the Regulations Government Number 71 of 2019 concerning with condition legitimacy a agreement . Parents or guardians are responsible answer on agreement electronics that are done by child , responsibility answer the in law civil Indonesia known with draft vicarious liability (responsibility substitute ) which is set in Article 1367 of the Civil Code , in matter this parents can do payment on purchased products or follow intrusion from the party perpetrator business For repair error (filing return goods).